EFISIENSI PUPUK KANDANG ITIK PADA MASA TRANSISI DARI PERTANIAN KONVENSIONAL KE SISTEM PERTANIAN ORGANIK BAWANG MERAH (Allium ascalonicum L). - Kiky Narviastri Narviastri Arlinda Putri; SAPTO PRIYADI; SETIE HARIENI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2019)
ABSTRACT Red Onion (Allium ascalonicum L.) is one of the main vegetables in Indonesia and has many benefits. One of the efforts to increase local onion production through cultivation techniques is by giving dairy manure. This study aims to determine the dose duganakan efficient manure against the growth and yield of onions, knowing the effect of duck manure on soil fertility. This research was carried out in April to June 2018 in Nganjat Village, Polanharjo District, Klaten Regency. The altitude of 225 meters above sea level with gray Regosol soil type. This study uses a single factor method with the basic design of Complete Randomized Block Design (RAKL) and repeated 4 times with the following level; K1: duck manure 5 ton/ha, K2: duck manure 7.5 ton/ha, K3: duck manure 10 ton/ ha, K4: duck manure 12.5 ton/ha, K5: duck manure 15 ton/ha, K6 : duck manure 17.5 ton/ha, K7: duck manure 20 ton/ha. The results of this study indicate that: (1) The provision of duck manure with a level of 5 ton/ha up to 20 ton/ha showed no significant difference in the parameters of plant height, number of leaves, dry stover weight, number of tubers and the diameter of the planting. Whereas in the parameters of fresh stover weight, the number of planting bulbs, the weight of tubers of crop consumption showed significantly different results. For the parameters of tuber weight, the consumption of the plant and tubers show the results are very different. (2) In this study, the administration of 15 tons / ha K5 duck manure doses gave the best results on several parameters of onion growth and yield. Giving K1 5 tons / ha duck manure, it produces the lowest tuber which is 2,16 tons / ha while giving K6 duck manure 17.5 tons / ha increases the yield of red onion bulbs which is 6,45 tons / ha.(3) The provision of duck manure in addition to affecting the growth and yield of onion plants was able to increase the amount ofÂ N in the soil after harvest.